FORMULATION AND PHYSICAL EVALUATION OF EFFERVESCENT GRANULES OF MINT LEAF EXTRACT (Mentha x piperita L) AS STIMULANSIA - Herliningsih; Angga Anugra Diputra; Haty Latifah; Melinda Fuji Rahayu (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Indonesia is a country with a diverse biodiversity spread across various regions. Several types of plants in Indonesia can be utilised as herbal medicines. One such plant suitable for medicinal purposes is mint leaves (Mentha x piperita L.). The chemical content found in mint leaves includes essential oils that serve as stimulants. This research aims to determine whether mint leaf extract can be used to create an effervescent granule formulation. Effervescent granules are produced using the wet granulation method, incorporating the active ingredient of mint leaf extract with different concentrations: F0: without the addition of mint leaf extract; F1: mint leaf extract added with a concentration of 15%; and F2: mint leaf extract added with a concentration of 17%. The effervescent granule formula is then evaluated based on its physical characteristics. Phytochemical screening of mint leaves yielded positive results, indicating the presence of essential oils. All mint leaf extract formulations tested for physical evaluation met the specified criteria. Flow properties and angle of repose testing resulted in values between 2-3 seconds for flow properties and 35°-36° for the angle of repose. Compressibility testing produced results ranging from 5% to 15%, pH testing yielded results between 5 and 6, and dissolution time results ranged from 40 to 41 seconds. Keywords: Mint leaves, extraction, wet granulation, effervescent granules